2002
DOI: 10.1097/00042752-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Oral Salt Supplementation During Ultradistance Exercise

Abstract: Sodium ingestion was associated with a decrease in the extent of weight loss during the race. There was no evidence that sodium ingestion significantly influenced changes in [Na] or PV more than fluid replacement alone in the Ironman triathletes in this study. Sodium supplementation was not necessary to prevent the development of hyponatremia in these athletes who lost weight, indicating that they had only partially replaced their fluid and other losses during the Ironman triathlon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 33 publications
9
72
1
1
Order By: Relevance
“…7,18,27 In all these studies, drinking sodium-free solutions caused a marked decrease in plasma volume that was possibly more profound than sodium losses, resulting in normal blood sodium during exercise. When sodium was also provided, the conservation of plasma volume prevented an increase in blood sodium.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…7,18,27 In all these studies, drinking sodium-free solutions caused a marked decrease in plasma volume that was possibly more profound than sodium losses, resulting in normal blood sodium during exercise. When sodium was also provided, the conservation of plasma volume prevented an increase in blood sodium.…”
Section: Discussionmentioning
confidence: 94%
“…Vrijens and Rehrer 17 found that sodium-free fluid intake during 3 hours of low-intensity exercise at a rate to match fluid loss decreased plasma sodium compared with ingestion of a carbohydrate-electrolyte drink. However, Speedy et al 18 and Hew-Butler et al 19 reported that large amounts of sodium supplemented in the form of tablets (700 mg/h and 40 tablets that each contained 620 mg of table salt) during the Ironman triathlon did not confer any advantage in the preservation of serum sodium. It is important to note that in these studies, participants had a weight loss of about 4% at the end of the race.…”
mentioning
confidence: 99%
“…(Hew-Butler et al 2006) or to prevent EAH (Speedy et al 2002). A further limitation was that we did not determine plasma [Na ? ]…”
Section: Limitationsmentioning
confidence: 99%
“…Currently, there is insufficient evidence to support the suggestion that ingestion of sodium prevents or decreases the risk for EAH; neither is there any evidence that consumption of sports drinks (electrolyte-containing hypotonic fluids) can prevent the development of EAH (1,(35)(36)(37)(38)42,100,101). Again, most commercial sports drinks are hypotonic with a sodium content of 10 to 20 mmol/L (230 to 460 mg/L).…”
Section: Prevention Of Eahmentioning
confidence: 99%